A confirmatory factor analysis of the Ottawa Mental Skill Assessment Tool (OMSAT-3*) - Romanian version - Craciun, M.; Dobosi, S.; Pop Ioan, N.; Prode, C. (Human Movement, 2011)
The goal of this study was to assess the factorial validity of the Romanian version of the Ottawa Mental Skills Assessment Tool - 3* - OMSAT-3*. Basic procedures. Cross-sectional with self-reported questionnaire. The sample included 212 athletes (98 women, 114 men; age = 24.3) competing at international and national levels in different sports. Main findings. Confirmatory factor analysis of the Romanian version of the OMSAT-3* replicated the factor structure of the original instrument displaying an adequate level of goodness-of-fit. Conclusions. This study provided support for the factor structure of the Romanian version of the OMSAT-3*. This version expands the possibility of assessing the psychological resources of athletes in order to increase their performance and awareness of towards mental skills.